Technical efficiency of rice production in terai district of Nepal - Subedi, Sanjiv; Ghimire, Yuga Nath; Kharel, Meena; Adhikari, Surya Prasad; Shrestha, Jiban; Sapkota, Bibek Kiran (Journal of Agriculture and Natural Resources, 2020)
This paper aimed to estimate the technical efficiency of rice production, also identifying the factors affecting technical efficiency. Jhapa, the Terai district of Nepal, having the highest rice production in the country, was purposely selected for the study. The primary information was collected from 100 rice growing farmers, randomly selected from the sampling frame, using the pre-tested semi-structured interview schedule. Also, two Key Informant Surveys were done. Besides, the secondary information was collected by reviewing the related literatures. Descriptive statistics, stochastic frontier model with Cobb-Douglas production function, and tobit model were used for data analysis. The stochastic production frontier model revealed that with the increase in seed, chemical fertilizer, human labor, and tractor power by 1 percent, the rice yield increases by 0.25 (P<0.05), 0.15 (P<0.01), 0.13 (P<0.05) and 0.21 (P<0.01) percent respectively. The average technical efficiency of the rice growing farmers in the study area was estimated 92%; in addition, majority of the farmers (62%) were operating at an efficiency level of 0.91- 0.95 followed by 32% at 0.86- 0.90. The tobit regression model revealed that farming experience (P<0.01), membership of the organization (P<0.01), and major occupation being agriculture (P<0.05) have statistically significant and positive on technical efficiency; while, schooling years (P<0.05) and number of economically active family members (P<0.05) have statistically significant but negative effect. There is still scope to increase the rice yield through efficient use of available resources with existing technologies.